Local Application of Tanshinone IIA protects mesenchymal stem cells from apoptosis and promotes fracture healing in ovariectomized mice - Shao Cheng; Xiaohui Hu; Kanghui Sun; Ziyu Huang; Yongjian Zhao; Yueli Sun; Bo Zeng; Jing Wang; Dongfeng Zhao; Sheng Lu; Qi Shi; Yongjun Wang; et al. (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background Elderly patients suffering from osteoporotic fractures are more susceptible to delayed union or nonunion, and their bodies then are in a state of low-grade chronic inflammation with decreased antioxidant capacity. Tanshinone IIA is widely used in treating cardiovascular and cerebrovascular diseases in China and has anti-inflammatory and antioxidant effects. We aimed to observe the antioxidant effects of Tanshinone IIA on mesenchymal stem cells (MSCs), which play important roles in bone repair, and the effects of local application of Tanshinone IIA using an injectable biodegradable hydrogel on osteoporotic fracture healing. Methods MSCs were pretreated with or without different concentrations of Tanshinone IIA followed by H2O2 treatment. Ovariectomized (OVX) C57BL/6 mice received a mid-shaft transverse osteotomy fracture on the left tibia, and Tanshinone IIA was applied to the fracture site using an injectable hydrogel. Results Tanshinone IIA pretreatment promoted the expression of nuclear factor erythroid 2-related factor 2 and antioxidant enzymes, and inhibited H2O2-induced reactive oxygen species accumulation in MSCs. Furthermore, Tanshinone IIA reversed H2O2-induced apoptosis and decrease in osteogenic differentiation in MSCs. After 4 weeks of treatment with Tanshinone IIA in OVX mice, the bone mineral density of the callus was significantly increased and the biomechanical properties of the healed tibias were improved. Cell apoptosis was decreased and Nrf2 expression was increased in the early stage of callus formation. Conclusions Taken together, these results indicate that Tanshinone IIA can activate antioxidant enzymes to protect MSCs from H2O2-induced cell apoptosis and osteogenic differentiation inhibition. Local application of Tanshinone IIA accelerates fracture healing in ovariectomized mice.